2021
DOI: 10.15184/aqy.2021.75
|View full text |Cite
|
Sign up to set email alerts
|

Sika deer in Bronze Age Guanzhong: sustainable wildlife exploitation in ancient China?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Ancient texts and archaeological evidence indicate that hunting, in particular, was a significant social activity during the Shang and Zhou dynastic periods (Cheng et al, 2017;Fiskesjo€, 2001). Most importantly, faunal evidence from Sunjia and Xitou indicates that wild taxa, especially deer, were exploited for tool-making, supporting Li et al (2021)'s argument of a shift occurred Frontiers in Earth Science frontiersin.org in the cervids regional exploitation, from meat to antlers. The discovery of some unworked post-cranial elements from deer associated with tools made of antlers-and to a lesser extent, bones and teeth-and debris suggests that local residents hunted cervids and produced artefacts locally.…”
Section: Figurementioning
confidence: 75%
See 1 more Smart Citation
“…Ancient texts and archaeological evidence indicate that hunting, in particular, was a significant social activity during the Shang and Zhou dynastic periods (Cheng et al, 2017;Fiskesjo€, 2001). Most importantly, faunal evidence from Sunjia and Xitou indicates that wild taxa, especially deer, were exploited for tool-making, supporting Li et al (2021)'s argument of a shift occurred Frontiers in Earth Science frontiersin.org in the cervids regional exploitation, from meat to antlers. The discovery of some unworked post-cranial elements from deer associated with tools made of antlers-and to a lesser extent, bones and teeth-and debris suggests that local residents hunted cervids and produced artefacts locally.…”
Section: Figurementioning
confidence: 75%
“…The relative paucity of wild taxa in our sites is in line with regional zooarchaeological and paleodietary research, which has shown that while hunting and fishing were practiced in the Neolithic, their importance declined during the Longshan period, possibly due to population growth and the increasing demand for meat, both for consumption and ritual purposes (Cheng et al, 2017). The decrease continued during the Late Shang period, when hunting and fishing may have become less related to the need for food (Li et al, 2021;Festa and Monteith, 2022) (Figure 9; Supplementary Table S3). Ancient texts and archaeological evidence indicate that hunting, in particular, was a significant social activity during the Shang and Zhou dynastic periods (Cheng et al, 2017;Fiskesjo€, 2001).…”
Section: Figurementioning
confidence: 99%
“…Dadiwan represents sustainable millet-pig agriculture in the Yellow River Valley (Yang et al 2022), where the hunting of cervids was obviously a supplementary though indispensable part of Yangshao subsistence. Pingliangtai Longshan societies followed the earlier Yangshao bone-working traditions in using cervid metapodials, which were also regular raw materials in the Bronze Age (Li 2018; Li et al 2021) (Table S8).…”
Section: Discussionmentioning
confidence: 99%
“…10000-2000 BC). Sika deer remains have been found in sites across China (Figure 1) (Institute of Archaeology Chinese Academy of Social Sciences, 1991; Institute of Archaeology Chinese Academy of Social Sciences, 1994; Institute of Archaeology Chinese Academy of Social Sciences, 1995; Henan Provincial Institute of Relics and Archaeology, 1999;Zhang et al, 1999;Zhejiang Provincial Institute of Cultural Relics and Archaeology, 2004;Zhang and Hung, 2008;Innes et al, 2009;Ren and Wu, 2010; Institute of Archaeology Chinese Academy of Social Sciences, Institute of Earth Environment Chinese Academy of Sciences, 2011; Wu et al, 2012), and usually take up a rather high proportion in the faunal assemblage (e.g., Henan Provincial Institute of Relics and Archaeology, 1999;Zhejiang Provincial Institute of Cultural Relics and Archaeology, 2003;Yuan and Yang, 2004;Wang, 2011;Song, 2017;Song, 2019;Li et al, 2021). The hunting strategies of sika deer have been discussed in the past few years, featuring the middle Yellow River region which was an important prehistoric cultural center in China.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the Wayaogou site (3400-2700 BC) suggested that deer hunting was organized according to seasonality and the conditions of the deer population (Wang, 2011;Wang et al, 2014). A recent research on the Zaoshugounao (1250-1050 BC) sika deer remains reveals a sustainable hunting strategy that took place in the Bronze Age (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%